Manifestation of Circular Economy in Repurposable Green Furniture Design, A Project-Based Learning by Interior Design Student - Triatmodjo, Suastiwi; Nurcahyo, Mahdi (Mudra Jurnal Seni Budaya, 2025)
This article reveals the embodiment of circular economy in interior design students' design of reused green furniture. The circular economy is becoming important, mainly in dealing with the problem of inorganic waste. The main focus is how the circular economy concept can be taught through actual practice, where students collaborate with stakeholders, namely TPS3R and the green industry, to design environmentally friendly and sustainable furniture. This applied research uses the double-diamond method from the UK Design Council to guide the design process, including Discovery, Definition, Development, and Delivery, emphasizing the first diamond for field research and the second diamond for design development. This method has enabled students to understand and practically apply circular economy principles. The applied research was conducted over 16 weeks for field research and studio work on campus. Although all the research results are not yet satisfactory, they show that this project-based learning approach effectively improves students' understanding of sustainability and innovation in furniture design. In addition, the collaboration with the green industry also enriched students' learning experiences and strengthened the link between education and industrial practice in sustainable design.